Consistency of demographic trade‐offs across 13 (sub)tropical forests. (12th May 2022) - Kambach, Stephan; Condit, Richard; Aguilar, Salomón; Bruelheide, Helge; Bunyavejchewin, Sarayudh; Chang‐Yang, Chia‐Hao; Chen, Yu‐Yun; Chuyong, George; Davies, Stuart J.; Ediriweera, Sisira; Ewango, Corneille E. N.; Fernando, Edwino S.; et al.
Abstract: Organisms of all species must balance their allocation to growth, survival and recruitment. Among tree species, evolution has resulted in different life‐history strategies for partitioning resources to these key demographic processes. Life‐history strategies in tropical forests have often been shown to align along a trade‐off between fast growth and high survival, that is, the well‐known fast–slow continuum. In addition, an orthogonal trade‐off has been proposed between tall stature—resulting from fast growth and high survival—and recruitment success, that is, a stature−recruitment trade‐off. However, it is not clear whether these two independent dimensions of life‐history variation structure tropical forests worldwide. We used data from 13 large‐scale and long‐term tropical forest monitoring plots in three continents to explore the principal trade‐offs in annual growth, survival and recruitment as well as tree stature. These forests included relatively undisturbed forests as well as typhoon‐disturbed forests. Life‐history variation in 12 forests was structured by two orthogonal trade‐offs, the growth−survival trade‐off and the stature−recruitment trade‐off. Pairwise Procrustes analysis revealed a high similarity of demographic relationships among forests. The small deviations were related to differences between African and Asian plots. Synthesis . The fast–slow continuum and tree stature are two independent dimensions structuring many, but not all tropical tree communities. Our discovery of the consistency of demographic trade‐offs and life‐history strategies across different forest types from three continents substantially improves our ability to predict tropical forest dynamics worldwide. Abstract : All species must balance their allocation to growth, survival and recruitment, resulting in different life‐history strategies for partitioning resources to these demographic processes. Across 13 (sub)tropical forests, the diversity of life‐history strategies in tropical tree communities is often, but not always, structured along two independent dimensions that are related to the fast–slow continuum and to a gradient in tree stature. Editor's Choice Zusammenfassung: Individuen aller Arten müssen ihrer Ressourcen zwischen Wachstum, Überleben und Nachwuchsrekrutierung allozieren. Baumarten haben, evolutionär bedingt, verschiedene biologische Strategien entwickelt, wie sie ihre Ressourcen auf diese wichtigen demografischen Prozesse verteilen. In tropischen Wäldern lassen sich die biologischen Strategien der Bäume oft entlang eines Gradienten anordnen, welcher Arten mit schnellem Wachstum von Arten mit langem Überleben trennt, i.e. das bekannte Fast‐Slow‐Kontinuum. Ein weiterer orthogonaler Trade‐off welcher Arten die durch schnelles Wachstum und langes Überleben eine hohe Statur erreichen können von solchen Arten trennt, die eine hohe Rekrutierungsrate vorweisen (i.e. ein Statur‐Rekrutierungs‐Trade‐off) wurde bisher zwar postuliert, aber es wurde noch nicht geklärt, ob die tropischen Wälder auch global von diesen beiden unabhängigen Dimensionen der biologischen Strategien strukturiert werden. In dieser Studie haben wir die Daten von 13 großflächigen und langfristigen Plots in tropischen Wäldern über drei Kontinente analysiert und die vorherrschenden Trade‐offs zwischen den jährlichen Wachstums‐, Überlebens‐ und Rekrutierungsraten sowie der Statur der lokalen Baumarten bestimmt. Die untersuchten Flächen umfassten dabei relative ungestörte, sowie Taifun‐gestörte Wälder. In zwölf dieser Wälder ordneten sich die biologischen Strategien der lokalen Baumarten entlang zweier orthogonaler Trade‐offs an, einem Trade‐off zwischen Wachstum und Überleben und einem Trade‐off zwischen Statur und Rekrutierung. Anschließende paarweise Procrustes‐Analysen zeigten eine hohe Ähnlichkeit in den Korrelationen zwischen den artspezifischen demografischen Raten zwischen diesen unterschiedlichen Wäldern. Wir fanden auch kleinere, aber signifikante Unterschiede, zwischen den Wäldern in Afrika und Asien. Synthesis . Das Fast‐Slow‐Kontinuum und die Statur der Baumarten stellen zwei unabhängige Dimensionen dar, welche viele, aber nicht alle tropischen Baumgemeinschaften strukturieren. Unsere Ergebnisse zur Übereinstimmung der demographischen Trade‐offs und den resultierenden biologischen Strategien über Wälder und Kontinente hinweg, ermöglicht es uns in Zukunft die Entwicklung von tropischen Wäldern weltweit besser vorherzusagen.